Discourse recovery after severe traumatic brain injury: exploring the first year. (28th January 2019) - Elbourn, Elise; Kenny, Belinda; Power, Emma; Honan, Cynthia; McDonald, Skye; Tate, Robyn; Holland, Audrey; MacWhinney, Brian; Togher, Leanne
ABSTRACT: Objectives: Although much is known about discourse impairment, little is known about discourse recovery after severe traumatic brain injury (TBI). This paper explores discourse recovery across the critical first year, controlling for pre-injury, injury and post-injury variables. Design and methods: An inception cohort comprising 57 participants with severe TBI was examined at 3, 6, 9 and 12 months post-injury and compared to a cross-section of matched healthy control participants. A narrative discourse task was analyzed with main concept analysis (MCA). A mixed linear model approach was used to track recovery controlling for pre-injury, injury and post-injury variables. Results: An upward trajectory of recovery was observed, with peak periods of improvement between 3–6 and 9–12 months and all time points were significantly below controls. Years of education and PTA duration were significant covariates in the recovery model. Presence of aphasia also influenced the recovery model. Conclusions: Individuals with TBI typically improve over the first year, however many will continue to have discourse deficits at 12 months. Years of education, PTA duration and aphasia should be considered when planning services. The 3–6- and 9–12-month periods may offer optimal periods for discourse recovery and increased supports may be beneficial between 6-9 months.